A mixed methods protocol to investigate medication adherence in patients with rheumatoid arthritis of White British and South Asian origin - Karim Raza; Peter Nightingale; Karen Shaw; Rob Horne; Kanta Kumar; Sheila Greenfield; Paramjit Gill (BMJ Open)
Background Low adherence to medicines is an important issue as up to 40% of patients with chronic diseases do not take their medications as prescribed. This leads to suboptimal clinical benefit. In the context of rheumatoid arthritis, there is a dearth of data on adherence to disease-modifying antirheumatic drugs among minority ethnic groups. This study aims to assess the relationship between adherence to medicines and biopsychosocial variables in patients with rheumatoid arthritis of South Asian and White British origin.Methods/analysis A mixed methods approach will be used, encompassing a cross-sectional survey of 176 patients collecting demographic and clinical data, including information on adherence behaviour collected using a series of questionnaires. This will be followed by indepth qualitative interviews.Ethics and dissemination This study has been approved by the South Birmingham (10/H1207/89) and Coventry and Warwickshire (12/WM/0041) Research Ethics Committees. The authors will disseminate the findings in peer-reviewed publications.